2018
DOI: 10.1111/cmi.12841
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofCandida albicansregulatory genes governing mucosal infection

Abstract: The fungus Candida albicans thrives on a variety of human mucosae, yet the fungal determinants that contribute to fitness on these surfaces remain underexplored. Here, by screening a collection of C. albicans deletion strains in a mouse model of oral infection (oropharyngeal candidiasis), we identify several novel regulatory genes that modulate the fitness of the fungus in this locale. We investigate in detail the interplay between the host mucosa and one of the identified mutants and establish that the C. alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Secretion of proinflammatory mediators such as cytokines and chemokines (G-CSF, GM-CSF, IL-1α, IL1β, IL-6, IL-8, and CCL5) by epithelial cells, signal the recruitment of phagocytic cells, including neutrophils, macrophages and dendritic cells (DCs) to the site of infection [109][110][111][112][113][114]. Several comprehensive reviews on C. albicans and host cells and the immune response during C. albicans mucosal infection were recently published [27,108,115]. Here, we focus on highlighting oral local innate immune defenses that play a crucial role in maintaining Candida in its commensal state in the oral cavity.…”
Section: Host Immune Responsementioning
confidence: 99%
“…Secretion of proinflammatory mediators such as cytokines and chemokines (G-CSF, GM-CSF, IL-1α, IL1β, IL-6, IL-8, and CCL5) by epithelial cells, signal the recruitment of phagocytic cells, including neutrophils, macrophages and dendritic cells (DCs) to the site of infection [109][110][111][112][113][114]. Several comprehensive reviews on C. albicans and host cells and the immune response during C. albicans mucosal infection were recently published [27,108,115]. Here, we focus on highlighting oral local innate immune defenses that play a crucial role in maintaining Candida in its commensal state in the oral cavity.…”
Section: Host Immune Responsementioning
confidence: 99%
“…The EasySep TM Human Neutrophil Enrichment Kit (StemCell Technologies, Inc.) was used to isolate human neutrophils from whole blood of healthy donors (kindly provided by the Department of Transfusion Medicine, University Hospital W€ urzburg) following the supplier's protocol. The neutrophil killing assay was carried out as reported (Meir et al, 2018). Briefly, 7 3 10 5 neutrophils were seeded in supplemented RPMI 1640 medium (2% human serum) in 24-well plates.…”
Section: Neutrophil Killing Assay and Imagingmentioning
confidence: 99%
“…Of the 153 direct target genes in this network that are upregulated during GI colonization and disseminated infection, 108 of them are bound by the Rtg1/3 heterodimer (Peŕez et al, 2013), highlighting the central role that Rtg1/3 plays in this network. We note that a subsequent study by the same group identified five transcriptional regulators that influence fitness in an oropharyngeal candidiasis model (Cup9, Zcf8, Zcf21, Zcf27, and Orf19.217), and identified a set of genes that are differentially regulated in response to deletion of CUP9 (Meir et al, 2018). We did not include these data in our analyses since binding experiments that would be necessary to integrate these additional regulators into the commensal-pathogen transcriptional circuit have not been performed.…”
Section: Referencesmentioning
confidence: 99%